Right To Information As A Means Of Protection Information Needs - Sattarov, Vitaly D.; Stus, Nina V.; Goncharov, Igor A.; Kuksin, Ivan N.; Markhgeym, Marina V. (Cuestiones Políticas, 2020)
This article refers to a comprehensive vision of the right to information as the main means of legal protection of the information needs of citizens in general. Based on psychological assumptions, the author justifies the importance of such needs in the life of modern society. The article details the issue of creating and guaranteeing the correct functioning of a special authorized administrative body, to act as an instance of appeal and supervision in the course of the legal regulation of information and the underlying legal relationships. By way of conclusion, the authors especially emphasize the need to overcome the culture of secrecy, a type of undemocratic government, and refer to other requirements and accepted standards in this area to guarantee the enjoyment and enjoyment of this right at all times.